Should employment authorities worry about mergers and acquisitions? - David N. Margolis (Institute for the Study of Labor (IZA), 2006)
This paper considers the role mergers and acquisitions have on employment. First, it considers the importance of different aspects of compensation policy and human resource management practices for distinguishing acquired and acquiring firms. Second, it examines which individuals from which firms remain with the newly created entity after the takeover. Using a unique employer-employee linked data set for France, we find that very few observable workforce or compensation characteristics distinguish acquired from acquiring firms ex-ante. Nevertheless, the human resources department seems to be quite active in the post-takeover period, with employees of the acquired firm being less likely to remain with the new entity in the short term after takeover than those of the acquiring firm and with the differences between the two types of firms disappearing after 3 years. The workers with characteristics that tend to be associated with the fastest subsequent job finding in the displaced worker literature are also those who tend to be overrepresented among the individuals who separate from their employer post-takeover. Finally, as both acquired and acquiring firms differ from firms not involved in takeover activity in a similar manner, employment authorities may be able to anticipate the regions in which takeovers are more likely to occur by looking at the financial accounts of firms with particular characteristics that have local establishments.
Keywords: G34; J21; J23; J31; J63; L29; M51; 330; employment; takeovers; linked employer-employee data; Übernahme; Beschäftigungseffekt; Abfindung; Personalwirtschaft; Frankreich